Safeguarding the Therapeutic Alliance: Managing Disaffiliation in the Course of Work With Psychotherapeutic Projects - Guxholli, Aurora; Voutilainen, Liisa; Peräkylä, Anssi (Frontiers in Psychology, 2021)
Therapeutic alliance is a central concept in psychotherapeutic work. The relationship between the therapist and the patient plays an important role in the therapeutic process and outcome. In this article, we investigate how therapists work with disaffiliation resulting from enduring disagreement while maintaining an orientation to the psychotherapeutic project at hand. Data come from a total of 18 sessions of two dyads undergoing psychoanalytic psychotherapy and is analyzed with conversation analysis. We found that collaborative moves deployed amidst enduring disagreement can assist the therapist in furthering the disagreement as part of the ongoing psychotherapeutic project. Relying on their collaborative format, therapists utilize collaborative moves to temporarily mend the disaffiliation without necessarily changing their position and re-affiliating with the patient. We show how the relation between the therapist and the patient gets transformed in the moment-by-moment work accomplished in the psychotherapeutic talk.